Penerapan PI Hole DNS Server Sebagai ADS-Blocker Dan Sistem Filtering Website Pada Jaringan Hotspot - okky abdurahman; Toibah Umi Kalsum; Riska Riska (Jurnal Media Infotama, 2022)
Abstract This research aims to build a Hotspot network infrastructure that is free from advertisements to maximize bandwidth usage, implement a virus prevention system by filtering websites, and reduce router performance in hotspot networks. This research uses the Network Development Life Cycle (NDLC) method. By using the research method, it is hoped that the author can define the process cycle of designing or developing a computer network system, especially in the process of implementing the Pi Hole DNS server as an ads-blocker and website filtering system on a hotspot network. The results of this study indicate that the application of a pi hole DNS server on a hotspot network can block advertisements on sites visited via a web browser on a hotspot network. In addition, the pi hole DNS server can also perform filtering on advertising provider sites and the pi hole DNS server does not reduce the quality of service on the hotspot network. Keywords: NDLC, pi hole, android, network, hotspot.